2012
DOI: 10.1080/10615806.2011.603048
|View full text |Cite
|
Sign up to set email alerts
|

The impact of uncertainty and communal coping on mental health following natural disasters

Abstract: Feelings of uncertainty are a central feature of the disaster experience. Surprisingly, though, there is very little systematic quantitative research about the impact of uncertainty on disaster survivors. Moreover, communal coping has increasingly received attention as a potential buffer of the negative effects of stressors but that literature is also limited in its application to disasters. This investigation applies research in the domain of uncertainty, together with the Theoretical Model of Communal Coping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
127
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 150 publications
(140 citation statements)
references
References 37 publications
10
127
1
2
Order By: Relevance
“…Another communication behavior, seeking support, is also characteristic of communal coping strategies as reported by Ibañez, Buck, Khatchikian, and Norris (2004) in their study of Mexican disaster survivors. Afifi et al (2012) found wildfire evacuees engaged in more communal coping efforts than non-evacuees. They further concluded that communal coping acted as a buffer against uncertainty and mental health for evacuees.…”
Section: Communal Copingmentioning
confidence: 95%
See 1 more Smart Citation
“…Another communication behavior, seeking support, is also characteristic of communal coping strategies as reported by Ibañez, Buck, Khatchikian, and Norris (2004) in their study of Mexican disaster survivors. Afifi et al (2012) found wildfire evacuees engaged in more communal coping efforts than non-evacuees. They further concluded that communal coping acted as a buffer against uncertainty and mental health for evacuees.…”
Section: Communal Copingmentioning
confidence: 95%
“…Because disaster recovery produces a communal, or co-owned, experience (Afifi et al, 2012) and a recognition that others' opinions and collective action will address a problem (Afifi et al, 2006), it seems a prime context for viewing communal coping behaviors. Communal coping is most applicable to groups who experience a unified stressor such as a natural disaster and must collectively confront it (Afifi et al, 2006).…”
Section: Communal Copingmentioning
confidence: 98%
“…These include indigenous concerns [33,70,71], examination of different fire management discourses [72-74, 75•, 76], and understanding the physical and mental health impacts of experiencing a wildfire event [54,[77][78][79][80][81][82]. In addition, a number of articles in the Australian literature have begun to explore the role of land use planning in mitigating fire risk [58,83,84] and how gender dynamics can influence preparedness and management dynamics [85,86].…”
Section: Experiencing and Recovering From A Wildfirementioning
confidence: 99%
“…However, most hospitals are normally late in their preparedness and giving appropriate responces. This delay is mostly because of financial problems and inappropriate understanding of the status of a hospital in giving services during the incidents [2].…”
Section: Introductionmentioning
confidence: 99%
“…History proves that human communities have always been involved in different types of disasters. More than 600 disasters are recorded annually, accounting for more than 90% causalties in developing countries, which indicate an essential threat [2].…”
Section: Introductionmentioning
confidence: 99%